Yeast population dynamics on air exposure in total mixed ration silage with sweet potato residue. (2nd June 2020) - Jiang, Di; Niu, Dongze; Zuo, Sasa; Tian, Pengjiao; Zheng, Mingli; Xu, Chuncheng
Abstract: To investigate the yeast population dynamics during air exposure in total mixed ration (TMR) silage containing sweet potato residue. TMR were ensiled in laboratory silos (1 kg) with or without two lactic acid bacteria strains, Lactobacillus plantarum (LP), and Lactobacillus amylovorus (LA). Fermentation characteristics were measured and yeast population was investigated by ITS1 region gene sequencing using Illumina MiSeq platform. All treatments were well ensiled, and L. amylovorus improved aerobic stability. During aerobic exposure, Pichia kudriavzevii was detected with increased relative abundance in all treatments and more relative abundant in LP. Pichia fermentans was more relative abundant in control. Higher relative abundance of Pichia anomala was detected in deteriorating LP. The relative abundance of Pichia ohmeri increased during later aerobic exposure in the control and LA, with a significant increase in the count of yeast population. Despite Cryptococcus was detected more relative abundant during early stage of aerobic exposure, the yeast population was below the detection limit. Aerobic deterioration was characterized by an increase in operational taxonomic units of Pichia . High relative abundance of P. anomala and P. kudriavzevii made aerobic deterioration easier. Inhibition of P. fermentans might be an effective strategy for improving the aerobic stability to some instance.